High-Throughput Optimization of Effective Microbes Nutrient Formulation via Automated Media Optimization System (AMOS) - I Saharuddin, A; Z M N Rashid, N; S Mohd Noor, N; S Abdul Rahman, N; Ismail, A; R Wan Abdul Razak, W; Pardi, F; H Jawad, A.; Ismail, K; A Radzun, K (International Journal of Engineering and Technology, 2019)
Fortification of effective microbes (EM) such as Pediococcus acidilactici and photosynthetic bacteria in fertilizer and animal feed exhibiting effective outcomes in enhancing crops and livestock production as well as upholds sustainable agriculture concept. However, the productivity of the EM biomass stocks is unsurpassed to the demand due to non-optimized media. In this study, two sets of nutrient pair comprising of beef extract-manganese and yeast extract-glucose for P. acidilactici and photosynthetic bacteria respectively were studied. The optimum media formulated was based on the highest growth rate in 96-microwell plate system were subsequently tested in 1 L cultures volume for EM biomass production. Results showed that growth rate and dry weight of P. acidilactici in media supplemented with 64 g/L beef extract (0.145 h-1, 0.243 g) and 0.28 g/L manganese (0.1134 h-1, 0.32 g) were higher compared to control medium with an increment of 17.39 % and 54.59 % biomass productivity as compared to MRS medium respectively. Meanwhile, the growth rate and dry weight for Photosynthetic bacteria in media supplemented with 6.63 g/L glucose (0.2538 h-1, 0.167 g) and 0.44 g/L yeast extract (0.2733 h-1, 0.163 g) recorded 11.3 % and 8.73 % biomass productivity increment in comparison to the HCH medium.Â Â